Examining the Perceived Sports Literacy of Physical Education Teachers, Trainers and Sports Managers in Terms of Various Variables - Meral Demir,; Mümine Soytürk, (Journal of Educational Issues, 2024)
Introduction and Purpose: UNESCO stated that literacy in the most general sense should include not only reading and writing, but also components of knowledge, thinking, communication, language, culture, and social practice (as cited in Lounsbery & McKenzie 2015). The main purpose of this study is to examine the perceived sports literacy of physical education teachers, trainers, and sports managers in terms of various variables. Furthermore, the validity and reliability level of the scale used in the study, developed by Sum et al., (2016) and adapted into Turkish by Ülker (2019), is examined in the subject group. Method: 103 physical education teachers, 55 trainers and 28 sports managers working in Manisa participated in the study. The “Perceived Sports Literacy Scale” (PSLS) and “Personal Information Form” were used to obtain the data. The data were evaluated using the Mann-Whitney test and Kruskal-Wallis test, internal consistency for reliability, and exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) for construct validity. Results: The gender and team supporter variables did not make a difference to PSLS scores. PSLS scores in all sub-dimensions were found to be higher and significant for those who did regular physical activity (RPA) compared to those who did not, while “confidence in psychomotor knowledge and ability” and “communication and lifelong sports consciousness” scores of trainers were found to be higher and significant compared to those of other occupational groups. As a result of the EFA and CFA analysis, it was seen that the scale was divided into 17 items and 3 sub-dimensions. Conclusion: It was concluded that doing RFA and being a trainer were effective in having higher PSLS scores than those of other participants, while the gender and team supporter variables were ineffective. The scale is a measurement tool that provides psychometric qualities to measure the sports literacy levels of sports sector employees.